Toward a reform framework for good governance focus on anti-corruption - Brillantes, Alex B., Jr (Philippine Journal of Public Administration, 2010)
The experience of the Philippines in the continuing efforts to address graft and corruption, red tape, and inefficiencies in the bureaucracy is the basis in designing a framework for reform to promote accountability and transparency. The following are the areas of reform: (1) reforms in institutions and structures, including reforms in organizations, processes, and procedures; (2) reforms in mindsets, paradigms, and behavior; (3) reforms in leadership (at various levels); and (4) reforms in citizens, i.e., citizens' engagement and/or citizens' participation. The authors begin with the contextualization of corruption in the Philippines, along with its causes and effects, and a discussion of issues and challenges of corruption in the Philippines, along with its causes and effects, and a discussion of issues and challenges of corruption. They examine how the four imperatives of reform can contribute in minimizing if not to totally eradicating corruption and in promoting good governance in the country.